Nanochemistry - Sergeev, G. B.; Klabunde, Kenneth J. (Elsevier, 2013)
This book is devoted to nanochemistry: a branch of the actively developing interdisciplinary field of nanoscience. This branch of science studies the processes to production and reactions of nanoparticles and their compounds. It has been shown that such particles are of high activity and can undergo new and unusual chemical transformations. These transformations play an active role in our daily lives to provide reagents for self-cleaning glass surfaces and fabrics, different antiseptic coverings, sensors for monitoring the environment and catalysts preventing pollution. Nanochemistry covers the main studies of these reactions and reviews the work of leading scientists from different countries around the world. This book is the first monograph on nanochemistry, combining the elements of review and text book which allows for information on current and prospective directions in nanochemistry. Leads the reader through the theory, research and key applications of nanochemistry providing a thorough reference for researchers in this important growing area 40% more content than the first edition and an expanded author team provide a more comprehensive coverage Reviews important new advances in the field including organic nanoparticles and key methods for making nanoparticles e.g. Solvated Metal Atom Dispersion and self assembly techniques.